2013
DOI: 10.2147/ott.s53098
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of chronomodulated chemotherapy versus conventional chemotherapy with paclitaxel, carboplatin, and 5-fluorouracil in patients with recurrent and/or metastatic head and neck squamous cell carcinoma

Abstract: BackgroundChronomodulated chemotherapy has emerged as a new therapy as a result of recent studies focusing on the biological clock. It has been demonstrated that combination chronomodulated chemotherapy of platinum-based drugs and 5-fluorouracil (5-Fu) can significantly improve efficacy and reduce the incidence of adverse events in patients with metastatic colorectal cancer, as compared with conventional chemotherapy. However, the results may be different in different tumors. Recurrent and metastatic head and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Previous work has associated increased FASN expression with chemotherapy resistance and demonstrated a chemosensitizing effect of orlistat‐mediated FASN inhibition in human malignancies . We hypothesized that orlistat treatment would increase susceptibility of OSCC cells to treatment with carboplatin, a platinum‐based chemotherapy drug used frequently in oral cancer treatment in both feline and human patients . This hypothesis was not supported by our results; rather, an antagonistic effect of dual treatment was detected in all cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has associated increased FASN expression with chemotherapy resistance and demonstrated a chemosensitizing effect of orlistat‐mediated FASN inhibition in human malignancies . We hypothesized that orlistat treatment would increase susceptibility of OSCC cells to treatment with carboplatin, a platinum‐based chemotherapy drug used frequently in oral cancer treatment in both feline and human patients . This hypothesis was not supported by our results; rather, an antagonistic effect of dual treatment was detected in all cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The new interdiscipline generated by the integration of chronobiology and onco-molecular biology is expected to expand the knowledge about tumor occurrence and development, and may provide a new approach for tumor therapy ( 98 102 ). Tumor chronotherapy, which is the selection of the optimum treatment time to achieve the maximum curative effect and the minimum toxic and side effects based on the rhythm characteristics of tumor growth, has achieved satisfactory results in clinical practice ( 98 102 ). However, the association between clock genes and tumors remains to be fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Findings revealed that current cisplatin-based chronotherapy protocols show advantages in relieving side effects of chemotherapy in patients by directly influencing the chemo drug’s metabolism [ 37 ]. Similarly, chronomodulated chemotherapy of platinum-based drugs and 5-fluorouracil can significantly improve efficacy and reduce adverse events in patients with metastatic colorectal cancer; however, these results must be taken with caution as its effect may be different for the treatment of other solid tumors [ 38 ]. Nevertheless, what started as a growing understanding of the importance of biological timing for normal physiology and the pathophysiology of diseases like cancer is now a more comprehensive field that revolves around cancer-associated clock disruptions, clock-dependent mechanisms of cancer, and chronotherapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%